Assessing the Impact of Increasing Antimicrobial Resistance of Vibrio cholerae on the Future Trends of Cholera Epidemic. (4th December 2012) - Mushayabasa, Steady; Bhunu, Claver P.
Abstract : Cholera, an acute intestinal infection caused by the bacterium Vibrio cholerae, remains a major public health problem in many parts of Africa, Asia, and Latin America. A mathematical model is developed, to assess the impact of increasing antimicrobial resistance of Vibrio cholerae on the future trends of the cholera epidemic. Equilibrium states of the model are determined and their stabilities have been examined. The impacts of increasing antimicrobial resistance of Vibrio cholerae on the future trends of cholera epidemic have been investigated through the reproductive number. Numerical results are provided to support analytical findings.